A Case of Leukocytoclastic Vasculitis Caused by Listeria monocytogenes Bacteremia. (29th May 2016) - Bunker, Daniel R.; Sullivan, Timothy
Abstract : Importance. Infections can cause leukocytoclastic vasculitis. Observations. We report the case of a patient with a left ventricular assist device who presented with acute kidney injury and biopsy proven leukocytoclastic vasculitis. Blood cultures grew Listeria monocytogenes . The patient's rash improved with treatment of the underlying Listeria infection. Conclusion. Clinicians should be aware that there are a number of broad categories of disease associated with the histologic finding of vasculitis, including infection. It is important to keep in mind the risk factors of a particular patient when formulating a differential diagnosis. This is the first reported case of Listeria bacteremia causing leukocytoclastic vasculitis.